A dysregulation of glucose metabolism control is associated with carotid atherosclerosis in patients with coronary heart disease (CORDIOPREV-DIAB study). (October 2016) - Yubero-Serrano, Elena M.; Delgado-Lista, Javier; Alcala-Diaz, Juan F.; Garcia-Rios, Antonio; Perez-Caballero, Ana I.; Blanco-Rojo, Ruth; Gomez-Delgado, Francisco; Marin, Carmen; Tinahones, Francisco J.; Caballero, Javier; Ordovas, Jose M.; van Ommen, Ben; et al.
Abstract: Background and aims: Patients with coexisting coronary heart disease (CHD) and type 2 diabetes mellitus (T2DM) are at high risk of cardiovascular recurrence, however, it is not well established whether they exhibit an increased intima-media thickness of both common carotid arteries (IMT-CC). Furthermore, whether this relationship is inherent to T2DM or depends on glycemic control has not been tested in large cohorts. Our aim was to determine whether clinical categories and/or analytical markers of glucose metabolism control were associated with IMT-CC in CHD patients. Methods: 1002 patients aged 20–75 years, categorized into normal glucose tolerance (NGT), impaired fasting glucose (IFG), impaired glucose tolerance (IGT) or T2DM, underwent an oral glucose tolerance test (OGTT) and an IMT-CC measurement. Results: IMT-CC was higher in T2DM patients with HbA1c > 6.5% compared to T2DM patients with HbA1c < 6.5% ( p = 0.001), patients with IFG or IGT ( p < 0.001) and NGT ( p < 0.001). When age was considered, IMT-CC was influenced by glucose metabolism control only in e patients with age <61 years ( p < 0.01). In a multiple linear regression analysis, glucose concentration at 120 min, but not other OGTT time-points appeared as a significant independent contributor of IMT-CC ( p < 0.001). Moreover, a multiple logistic regression and the area under curve (AUC) of the ROC curve analysis showed a predictive power of glucose at 120 min to detect those CHD patients at the highest risk, defined as IMT-CC ≥ 0.7 mm (R 2 = 0.221; AUC = 0.761). Conclusions: Our results highlight the importance of properly controlling glucose metabolism in CHD patients, in younger populations in particular, providing an easy way of categorizing patients with an increased IMT-CC. Moreover, glucose concentration at 120 min could contribute to CVD risk and its determination could be used as a predictive tool to identify those CHD patients at the highest risk. Highlights: Glucose metabolism control is significantly associated with carotid atherosclerosis in coronary heart disease (CHD) patients. Age determines a differential response to glucose metabolism control related to intima media thickness of both carotid arteries (IMT-CC). Glucose at 120 min during an oral glucose tolerance test (OGTT) is a significant predictor of increased IMT-CC.